Strategi Pengelolaan Konten Instagram Sekolah dalam Membangun Citra dan Reputasi Lembaga Pendidikan - Awaliyah Zuliatun Najah; Aulia Ainurrochmah; Vresty Nur Afina; Ziana Candra Fajera (Yayasan Literasi Sains Indonesia, 2026)
Advances in digital technology have encouraged educational institutions to utilize social media as a means of communication, promotion, and institutional image building. Instagram has become one of the most widely used platforms due to its ability to reach broad audiences through engaging visual content. This study aims to analyze the role of Instagram as an educational marketing medium, the strategies for managing school Instagram content in building institutional image and reputation, as well as the supporting and inhibiting factors affecting its management. The study employed a Systematic Literature Review (SLR) method with a descriptive qualitative approach. Data were collected from relevant scientific articles, books, and academic documents and analyzed using content analysis techniques. The findings indicate that Instagram plays an effective role in increasing school visibility, expanding information dissemination, strengthening relationships with the community, and enhancing the image and reputation of educational institutions. Effective management strategies include content planning, publication scheduling, visual branding, and audience engagement. This study also proposes a conceptual model, namely the Synergistic Cycle of School Instagram Content Management, which demonstrates that these four strategies are interconnected and mutually reinforcing in building institutional image and reputation in a sustainable manner. Supporting factors include competent human resources, technological support, and institutional support, while inhibiting factors consist of limited human resources, inadequate content design skills, and inconsistent content publication. These findings highlight the importance of strategically managing digital resources to support effective educational branding in the digital era.